The brief introduction to Hinduism: Religion, philosophy, and ways of liberation - Herman, A L (Westview, 1991)
The book begins with the assumption that philosophies and religions exist primarily to cope with human problems. Chapter 1 examines three extremely different Hindu problem solvers of the twentieth century, namely, Mohandas Gandhi, Ramana Maharshi, and A. C. Bhaktivedanta. Chapter 2 presents three ancient traditions of Hinduism: first, in the archaeological remains of the Indus Valley civilization (2500-1800 B.C.E); second, to the sacred compositions, called the Vedas, of the Aryan invaders (1500-900 B.C.E.) who displaced that civilization; and third, to the secret teachings of the Upanisads (800-200 B.C.E.) that attempted to offer a new and revolutionary alternative to the Vedas. Chapter 3 turns from these three ancient traditions of Hinduism to the attempt that was made at synthesizing the Indus and pre-Vedic tradition, the Vedic tradition, and the Upanisadic tradition. The fouth and final chapter analyzes and summarizes the results of our investigations into the problem-identifying and problem-solving ways of Gandhi, Maharshi, and Bhaktivedanta, of the ancient traditions found in the Indus Valley civilization, the Vedas, and the Upanisads, and of the Bhagavad Gĩtã